Marxism and literary criticism - Eagleton, Terry 1943- (University of California Press, 1976)
Explores the growth of Marxist criticism in modern literary circles and demonstrates the role Marxism can play in creating a link between literature and historical conditions. Details major issues presented by this method of criticism and considers the work of such individuals as Plekhanov, Trotsky, Lenin, and Goldmann.